STRATEGI KOMISI PEMILIHAN UMUM PROVINSI DKI JAKARTA DALAM MENINGKATKAN PARTISIPASI PEMILIH KELOMPOK DISABILITAS (STUDI KASUS PEMILU PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019) - Rifki Fadillah (2023)
This study aims to explain how the strategy carried out by the DKI Jakarta Provincial Election Commission is in order to increase voter participation for groups of people with disabilities in the 2019 Presidential and Vice Presidential elections. The method used in this study is descriptive qualitative using primary data sources and secondary data. The author uses four analytical stages according to Miles & Huberman including: data collection, data reduction, data presentation, and drawing conclusions. This study discusses the strategies used by the KPU DKI Jakarta Province to increase the sensitivity of voters for groups with disabilities using political marketing theory through the Newman & Shet positioning approach which is divided into four strategic options, including: Strengthening strategies, rationalization strategies, persuasion strategies, and confrontation strategies. Implementation of the strategy is carried out through voter education socialization activities, optimizing the use of digital media, and using accessibility support facilities for groups of people with disabilities in DKI Jakarta. The final results of this study indicate that the DKI Jakarta Provincial Election Commission's strategy in increasing voter participation for groups of people with disabilities in DKI Jakarta in the 2019 Presidential and Vice-Presidential election has been implemented well because it has experienced a significant increase. The 2019 presidential and vice presidential elections carried out by groups of persons with disabilities in DKI Jakarta were at 81.87%. This amount exceeded the national target set by the KPU RI, which was 77.5%.